Differential Regulation of the Nodulation Zone by Silver Ions, L--(2-Amino-Ethoxyvinyl)-Glycine, and the skl Mutation in Medicago truncatula - Joko Prayitno; Ulrike Mathesius (HAYATI Journal of Biosciences, 2010)
Nodule formation in Rhizobium-legume symbiosis is negatively regulated by ethylene. Ethylene inhibitors such as L-a-(2-amino-ethoxyvinyl)-glycine (AVG) and silver ions (Ag+), the ethylene-insensitive sickle mutant, and transgenic plants were used to study ethylene-mediated responses in nodulation. The mode of action of ethylene inhibitors AVG and Ag+, and the skl mutation occur at different steps in ethylene biosynthesis and perception. Their effects on root growth and nodulation phenotypes, in particular nodule distribution along the primary root, were compared in this study. Ag+ and AVG treatments showed similar root growth responses to skl mutant. However, nodule distribution in the hypernodulating skl mutant is different from that of wild-type plants grown on either AVG or Ag+. AVG increased nodule numbers and widened the nodulation zone, while the skl mutant had an increased number of nodules within the susceptible zone of nodulation. Ag+ reduced nodule numbers, restricted the nodulation zone, and restored the nodulation phenotype of skl to that of the wild type.